Effect of natural zeolite as substrate filler on the properties of NBR/EPDM blend - Hesty Eka Mayasari; Noor Maryam Setyadewi (Majalah Kulit, Karet, dan Plastik, 2019)
The NBR/EPDM blend has a great ozone, oil, and heat resistance. Carbon black is the most commonly used filler material for rubber goods. But, it is less environmentally friendly and less healthy friendly. In this study, we will study the use of natural zeolite as a substitute for the filler. This blend was carried out by a two-roll mill and tested by rheometer and tensile strength tester. From the research that has been done, it is known that vulcanizate with carbon black is better than all of the vulcanizate using zeolite as filler substitute. Vulcanizate with CB provide the fastest curing time, the fastest reaction speed and also the best mechanical properties. Vulcanization with the 10 phr zeolite gives the optimum curing time and the best mechanical properties compared to the substitution of other fillers. This shows that 10 phr zeolite (16.7%) can be a suitable filling material for NBR/EPDM blend.